KARAKTERISTIK PENGERINGAN CABAI BERDASARKAN PERBEDAAN VARIETAS (Capsicum frustescens dan Capsicum annum) DAN DAYA OVEN MICROWAVE - Purbasari, Dian; Yosika, Nur Ida Winni; Pambudi, Akbar Setyo; Fitria, Yesi Ihsa (Jurnal Penelitian Sains dan Teknologi Indonesia, 2024)
Chili is a horticultural plant widely cultivated in Indonesia due to its high economic value. The most common chili is large red chili (Capsicum annuum) and bird's eye chili (Capsicum frutescens). The shelf life of chili and traditional post-harvest handling were challenges in chili agribusiness development. One method to extend chili shelf life is drying. This research uses microwave drying methods to determine the best variety and drying power to produce good-quality chili. This study aims to determine the moisture content, color, and drying rate of chili during the drying process. The results indicated that the shortest drying time was achieved at the highest power level of 695 W. At this power level, the moisture content of large red chili was reduced from 84.24% to 0.171% within 12–14 minutes. The moisture content of bird's eye chili at the highest power level of 695 W was reduced from 79.37% to 0.018%. The equilibrium moisture content (Me) with the fastest drying time was achieved at 695 W, with a value of 0.77% for large red chili in 12 minutes, and 0.43% for bird's eye chili in 14 minutes. The highest drying rates for large red chili and bird's eye chili were observed at the 695 W power level. The color properties of the dried chili included a lightness (L) range of 11.77-24.89, redness (a) range of 0.20-3.83, and yellowness (b) range of 0.83 - 2.40.